89.8k views
1 vote
-18=15-3(6t+5) solve for answer

User Dennis Huo
by
5.1k points

2 Answers

2 votes

Answer:


\huge\boxed{\boxed{t=1}}

Explanation:


-18=15-3(6t+5)\qquad|\text{subtract 15 from both sides}\\\\-18-15=15-15-3(6t+5)\\\\-33=-3(6t+5)\qquad|\text{divide both sides by (-3)}\\\\(-33)/(-3)=(-3(6t+5))/(-3)\\\\11=6t+5\qquad|\text{subtract 5 from both sides}\\\\11-5=6t+5-5\\\\6=6t\qquad|\text{divide both sides by 6}\\\\(6)/(6)=(6t)/(6)\\\\1=t\to\boxed{t=1}

User Noobsee
by
4.7k points
4 votes

Answer:

t = 1

Explanation:

First, distribute -3 to the parentheses:

-18 = 15 - 3(6t + 5)

-18 = 15 - 18t - 15

Add like terms, and solve for t:

-18 = -18t

1 = t

So, t = 1

User TommyBs
by
5.7k points